2018
DOI: 10.3758/s13423-018-1490-1
|View full text |Cite
|
Sign up to set email alerts
|

How often are thoughts metacognitive? Findings from research on self-regulated learning, think-aloud protocols, and mind-wandering

Abstract: Metacognitive monitoring refers to how people evaluate their cognitive performance. An extensive literature examines how accurately individuals engage in monitoring. The question of how often individuals engage in metacognitive monitoring has been largely neglected, although one might expect situational, group, and individual variability in monitoring frequency. We argue that this is a critical omission, given that the frequency of metacognitive monitoring might have important implications for monitoring accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 155 publications
0
14
0
Order By: Relevance
“…during learning, retrospectively during testing, or outside of the learning context altogether and via MC questionnaire scales), and the types of information the measures are intended to generate, variability between studies is not surprising. For example, offline measures reflect more stable trait-like characteristics indicating student awareness and potential use of MC strategies in their approach to solve math problems, while online measures capture thought processes associated with working through specific material (review by Jordano and Touron 2018). One important goal for optimising the potential for math achievement in school should focus on identifying MC strategies that will help students to identify areas of the curriculum that require additional attention or study (e.g., Son and Metcalfe 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…during learning, retrospectively during testing, or outside of the learning context altogether and via MC questionnaire scales), and the types of information the measures are intended to generate, variability between studies is not surprising. For example, offline measures reflect more stable trait-like characteristics indicating student awareness and potential use of MC strategies in their approach to solve math problems, while online measures capture thought processes associated with working through specific material (review by Jordano and Touron 2018). One important goal for optimising the potential for math achievement in school should focus on identifying MC strategies that will help students to identify areas of the curriculum that require additional attention or study (e.g., Son and Metcalfe 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that MC control and monitoring were most evident when children were asked to complete complex math problems. In a review of think-aloud methods, Jordano and Touron (2018) also reported that children's use of MC strategy increased with more complex and open-ended mathematical tasks.…”
Section: Metacognition and Math Performancementioning
confidence: 99%
“…Recent works (33,34) highlight the concept of meta-awareness (being aware of our current thinking) in the study of MW. Drescher et al (34) explored MW, meta-awareness, and cognitive control by three distinct tasks and showed that subjects with a higher metaawareness had a better cognitive control but detected less their MW.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works ( 33 , 34 ) highlight the concept of meta-awareness (being aware of our current thinking) in the study of MW. Drescher et al.…”
Section: Discussionmentioning
confidence: 99%
“…-Nov). This strategy is characterized by the integration of meta-cognitive knowledge about pain regulation (Jordano, Touron 2018) with a form of meta-cognitive monitoring centered on interoception. The belief that a flexible way to cope with pain works better than a rigid one stems from the evidence the more you let it go, the less you resist, the less pain affects you -Exp).…”
Section: Phc2: Cognitive Suppression and Metacognitive Volitional Conmentioning
confidence: 99%